1983
DOI: 10.1002/ajp.1350040107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testosterone on epididymal proteins in castrated rhesus monkeys

Abstract: The effect of testosterone on regulation of epididymal protein synthesis has been investigated in castrated rhesus monkeys (Mucaca mulatta). The proteins in the treated monkeys were characterized using polyacrylamide gel electrophoresis (under nondenaturing and denaturing conditions) and electrofocusing. At least four distinct proteins have been shown to be synthesized by the monkey epididymis under testosterone influence. Two of these proteins were detected following two days of testosterone treatment while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In contrast, only one report, using denaturing conditions of electrophoresis, records the changes in protein composition of spermatozoa during epididymal maturation or the role of epididymal proteins in this process in nonhuman primates (Young et al, 1985). Limited information is reported (Haider et al, 1983; Arslan et al, 1986) on the gross changes in protein composition of tissue cytosol of different segments of monkey epididymis using nondenaturing conditions of electrophoresis.…”
mentioning
confidence: 99%
“…In contrast, only one report, using denaturing conditions of electrophoresis, records the changes in protein composition of spermatozoa during epididymal maturation or the role of epididymal proteins in this process in nonhuman primates (Young et al, 1985). Limited information is reported (Haider et al, 1983; Arslan et al, 1986) on the gross changes in protein composition of tissue cytosol of different segments of monkey epididymis using nondenaturing conditions of electrophoresis.…”
mentioning
confidence: 99%
“…This investigation demonstrates the presence of at least five androgen-regulated proteins in the epididymal cytosol of the adult rhesus monkey. In a previous study using castrated imma-ture monkeys, androgen treatment has been shown to stimulate the synthesis of four proteins (characterized as bands B-E by PAGE) in the epididymal cytosol [12]. Similar androgendependent proteins have been identified in the epididymis of rat 16-43].…”
Section: Discussionmentioning
confidence: 81%
“…Contrary in rhesus monkeys both an elevation of testosterone in dominant and a depression in subordinate animals exist (Kling and Dunne -1973;Rose et al -1971Rose et al - ,1972Rose et al - ,1975. Evidence has been accumulated emphasizing the importance of testosterone for maintenance of the epithelium in the epididymis (Jones -1974, Haider et al -1983, Kumar and Panda -1983 as well as in the prostate gland (Timms -1983).…”
Section: Effects Of Enforced Coexistencementioning
confidence: 99%